Analysis of Patient Satisfaction on the Quality of Pharmaceutical Service at the Pharmaceutical Installation - Kharisma Jayak Pratama; Isna Nur Khasanah; Dewi Weni Sari; Nabilah Hanim Mohd Sabri (Global Health Science Group, 2023)
Consumer satisfaction with services can be measured by making comparisons between what is expected by consumers on the desired quality of a service based on the reality received or felt by consumers. Pharmaceutical services are supporting services and, at the same time, one of the main centers, providing more than 90% of health services in hospitals. Objective: The purpose of this study was to describe the level of patient satisfaction and expectations and to determine the overall level of visitor satisfaction with the services of the Muhammadiyah Hospital Pharmacy Installation Siti Khodijah Gurah Kediri. Method: This type of research is a quantitative descriptive study conducted on a set of objects with the aim of knowing the level of patient satisfaction and expectations of the services of the Muhammadiyah Siti Khodijah Gurah Hospital Pharmacy Installation, Kediri. The analysis of the collected data is then made in the form of tabulations and analyzed using the percentage formula. Analysis of satisfaction level scores in this study used the Likert scale answer format, which allows patients to answer at various levels (1-4) where each answer is given a weighted value with the following conditions: score 4 if the answer is